Huntress - Radley, A. E. (Heartsome Publishing, 2017)
"Amy is stuck in a rut. After graduating, she never left her temporary job at the motorway service station. Daily visits from a mysterious woman are the highlight of her days. Until one day, when the mystery woman vanishes. Amy investigates the disappearance and makes a shocking discovery. Suddenly, she's being framed and no-nonsense Claudia McAllister is being sent to arrest her. Will Amy's unique approach to evading capture prove successful?"--Amazon.com.